STUDY OF PERCEPTIONS AND THE ROLE OF ESP TEACHERS ABOUT EFFECTIVENESS OF ESP COURSES IN LANGUAGE TEACHER EDUCATION DURING PRE-AND IN-SERVICE TEACHING PRACTICE - Artishedar, Nesa; Najafi, Fatemeh; Najafi, Fatemeh; Najafi, Fatemeh; Bijani, Houman; Bijani, Houman; Bijani, Houman (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
It is believed that the time that the undergraduate students register in Teacher Education Program they have an extensive amount of experience, but English for specific purpose (ESP) teachersor pre-service ESP teachers are regarded as valuable resources for recognizing attitudes or perceptions of effectiveness of ESP teachers whose classless are taught by them. Pre-service teachers surely have several specific perceptions about their future career and the effectiveness of ESP teachers whose classes are being taught by them during practice teaching. If ESP teachers are asked the question why do you want to be anESP teacher? They may have different responses such as: I want to be an ESP teacher because I have a very good image of my teachers during my school period or I want to be a ESP teacher because I would like to follow the methods and procedures of effective teaching that my university teachers did during teaching specific courses. However, some might have an opposite perception. Anyway, this study tries to compare the perceptions of ESP teachers before (pre-service) and after (in-service) teaching period.